Examining the relationships between brand authenticity, perceived value, and brand forgiveness: The role of cross-cultural happiness - Papadopoulou, Christina; Vardarsuyu, Merve; Oghazi, Pejvak (Journal of business research, 2023)
•We demonstrate that brand authenticity positively affects brand forgiveness, which is mediated by perceived value.•Our moderated mediation findings revealed that the mediating effect is strengthened for higher cross-cultural happiness levels.•Interestingly, emotional value is the only aspect of perceived value that drives brand forgiveness when levels of cross-cultural happiness are low.•We also show a serial mediating effect of brand authenticity on purchase intentions via perceived value and forgiveness. Brand authenticity has attracted the growing attention of academics and practitioners for two decades. This study contributes to brand management literature by empirically investigating the impact of brand authenticity on purchase intentions through perceived value (functional, emotional, and social) and brand forgiveness using a 2 × 2 between- subjects experimental design with a sample of consumers from the UK and Turkey. The moderating role of cross-cultural happiness on the link between perceived value and brand forgiveness is also examined. Moderated mediation results demonstrate that brand authenticity positively affects brand forgiveness, and this effect is mediated by perceived value. In addition, cross-cultural happiness positively moderates the impact of perceived value on brand forgiveness. Findings further reveal a serial mediating effect of brand authenticity on purchase intentions via perceived value and brand forgiveness. This study has important theoretical implications and offers international brand and marketing managers practical insights.